The Hass Avocado Market in Japan: Challenges for Colombian Exporters (2021)
This article illustrates the admissibility of the Colombian Hass avocado in the Japanese market: The challenges of the fruit at the production and commercialization level in Colombia, the challenges in developing an innovative packaging that allows preserving the Hass avocado and, therefore, achieving effective commercialization in international markets, as well as the challenges in carrying out efficient monitoring of the crop in order to avoid the spread of quarantine pests, strictly regulated by Japan, to avoid damage within its territory. Finally, it also demonstrates the importance of the role of government institutions and avocado cooperatives in Colombia in providing support and training to producers for the optimal fulfillment of exports and opportunities in new markets, such as the Japanese market.